Prediction of anomalous LA-TA splitting in electrides - Leilei Zhang; Hua Y. Geng; Q. Wu (Matter and Radiation at Extremes, 2021)
Electrides are an emerging class of materials with excess electrons localized in interstices and acting as anionic interstitial quasi-atoms (ISQs). The spatial ion–electron separation means that electrides can be treated physically as ionic crystals, and this unusual behavior leads to extraordinary physical and chemical phenomena. Here, a completely different effect in electrides is predicted. By recognizing the long-range Coulomb interactions between matrix atoms and ISQs that are unique in electrides, a nonanalytic correction to the forces exerted on the matrix atoms is proposed. This correction gives rise to a longitudinal acoustic-transverse acoustic splitting in the acoustic branch of lattice phonons near the zone center, similar to the well-known longitudinal optical–transverse optical splitting in the phonon spectra of ionic compounds. The factors that govern this splitting are investigated, with isotropic fcc-Li and anisotropic hP4-Na as the typical examples. It is found that not all electrides can induce a detectable splitting, and criteria are given for this type of splitting. The present prediction unveils the rich phenomena in electrides and could lead to unprecedented applications.